Implementation of the PNM Program to Build a Prosperous Family Economy (Mekaar) in an Effort to Improve Community Economic Prosperity Through Access to Capital for SMEs in Duri Kosambi - Chaerunisa, Movita; Wahyunengsih (Faculty of Economics and Islamic Business State Islamic University of Palangka Raya, 2023)
One of the financing institutions in Indonesia in the form of BUMN is PT Permodalan Nasional Madani (Persero) or commonly abbreviated as PT PNM (Persero). PT PNM (Persero) was established by the Government on June 1, 1999 with the special task of empowering micro, small, medium enterprises and cooperatives (UMKMK). Increasingly growing and having carried out business transformation, in 2015 PT PNM (Persero) launched the product PNM Mekaar (Building a Prosperous Family Economy) which provides special services for underprivileged women who are ultra micro business actors, both those who want to start a business or develop a business. The method used in this study is a descriptive qualitative research method because most of the data used in this study came from interviews with research subjects in the form of sentences or narratives. The Mekaar Program or Fostering a Prosperous Family Economy is a program to help improve the welfare of Indonesian families, especially groups of underprivileged women. The approach is taken to customers or prospective customers by motivating them to want to do business by adhering to the principles of hard work, honesty, and discipline to achieve success and improve socio-economic status or welfare. The Mekaar program also emphasizes the importance of the group's role as a forum to promote harmony, kinship, and mutual cooperation. Mentoring and financing facilitation provided by Mekaar is also carried out using a group model. As a financing program, Mekaar targets women in the underprivileged category, who are required to form groups of 10-30 members. Loans are provided without collateral using the joint responsibility method, which means that if one member of the group is unable to pay the weekly installments, the payments are the responsibility of all group members.